ISOLATION AND EVALUATION OF NATIVE STRAINS OF PSEUDOMONAS FLUORESCENS FOR BIOLOGICAL CONTROL OF CHICKPEA WILT CAUSED BY FUSARIUM OXYSPORUMF. SP. CICERI - MADHUMITA PANDEY; SOBITASIMON (The Bioscan, 2015)
In this study, antagonistic effect of twenty isolates of Pseudomonas fluorescens isolated from rhizosphere of Chickpea was evaluated against Fusariumoxysporum f.sp. ciceri as potential bio-control agentin-vitro and in- vivo.Six isolates, Pf18 (80.1%), Pf4 (79.8%),Pf20(76.4%),Pf19(73%), Pf13 (72.6%) and Pf14 (70.3%) were selected according to their high antagonistic efficiency in in-vitro which was shown as maximuminhibition % in dual culture assay. Green house experiment the same six isolates effectively reduced the percentage of wilted plants, percentage ranges from 4-18% at 30 DAS, 14-30% at 60DAS and 30.6-39.4 % at 90 DAS and the best disease control was achieved by isolate Pf18 (41.75%) over control. In field trial isolate Pf14 was found significantly superior than other isolates in increasing the growth parameter and germination percentage (96.7-98%) over control of chickpea plant. These isolates significantly reduced the percentage of wilted plants (30.5-36.6 %) compared with untreated control (81.6%) at 90 DAS. Thus, our results indicate that native isolates of Pseudomonas fluorescens improve growth parameter in plants and can help in the bio control of pathogen.